Implementation of a digital game-based learning environment for elementary education - Almonte, Jason B.; Ramirez, Ceferino Gabriel R.; Tugade, Reynaldo R. (2010)
Video games have gained high popularity nowadays that researchers have taken an interest in its use as an educational medium. Recent trends have shown that students spend more time mastering a video game rather than doing one's homework. Studies have found that games have an attractive element that includes motivation, and engagement in a student. In a effort to exploit video games, researchers from different fields have delved into psychology, education and computer science in order to develop criteria and frameworks to integrate education into video games. Based on previous studies on educational game development, the project has developed video games for mobile handheld devices that covers topics from the Grade 6 Science curriculum. The games were developed for the Apple Ipod Touch and use a free and open source game engine, Cocos2D. A game framework was developed to enhance the game engine and foster rapid prototyping of games. Testing was done in two phases. The first was a functionality test on the game framework to verify that the components work. The second phase was qualitative beta testing to identify areas of the game that need to be improved, and the overall perception and acceptance of the game among target players. Moreover, the project investigated the critical elements of educational game design based from the test results in order to improve the framework for future development of educational games.
Thesis (B.S. Computer Engineering) -- University of the Philippines, Diliman
Keywords: Educational games; Education, Elementary -- Educational games; Open source software